2010
DOI: 10.1111/j.1525-142x.2010.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Splitting placodes: effects of bone morphogenetic protein and Activin on the patterning and identity of mouse incisors

Abstract: The single large rodent incisor in each jaw quadrant is evolutionarily derived from a mammalian ancestor with many small incisors. The embryonic placode giving rise to the mouse incisor is considerably larger than the molar placode, and the question remains whether this large incisor placode is a developmental requisite to make a thick incisor. Here we used in vitro culture system to experiment with the molecular mechanism regulating tooth placode development and how mice have thick incisors. We found that lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 49 publications
7
59
0
2
Order By: Relevance
“…4 J-M). The shift from a jawlength tooth band to a small restricted tooth bud when Notch signaling is inhibited in pufferfish is remarkably similar to the mouse incisor, which develops from an elongated placode that separates into multiple smaller placodes following bmp or activin manipulation (38). However, in contrast to mice, the formation of a single, restricted symphyseal tooth, rather than multiple separated teeth, after Notch inhibition suggests that the transition from a Diodontidae/Triodontidae-like beak to a pufferfish beak did not involve the coalescence of dental placodes.…”
Section: Discussionmentioning
confidence: 98%
“…4 J-M). The shift from a jawlength tooth band to a small restricted tooth bud when Notch signaling is inhibited in pufferfish is remarkably similar to the mouse incisor, which develops from an elongated placode that separates into multiple smaller placodes following bmp or activin manipulation (38). However, in contrast to mice, the formation of a single, restricted symphyseal tooth, rather than multiple separated teeth, after Notch inhibition suggests that the transition from a Diodontidae/Triodontidae-like beak to a pufferfish beak did not involve the coalescence of dental placodes.…”
Section: Discussionmentioning
confidence: 98%
“…It has been proposed, based on in vitro experiments, that the incisor versus molar identity of teeth is determined by the level of Bmp signaling ). However, this conclusion was challenged recently by the observation that inhibition of Bmp signaling caused partial splitting of the incisor placode resulting in the formation of two fused incisors rather than incisor to molar transformation (Munne et al 2010). The molecular basis of odontogenic competence in early jaw epithelium and later in the condensed dental mesenchyme remains elusive.…”
Section: Signaling Network Regulating Tooth Developmentmentioning
confidence: 98%
“…This is accompanied by spreading of Bmp4 expression to the lingual mesenchyme and results probably from a subsequent broadening of the dental field (Mikkola 2009a). The relative sizes of the mouse molars are influenced by activation and inhibition between successionally developing teeth (Kavanagh et al 2007), the size and number of mouse incisors is affected by fine-tuning Bmp signaling in the placodes (Munne et al 2010), and the continuous growth and enamel deposition in incisors can be modulated by the levels of Fgf, Activin, and Bmp signaling in the epithelial stem cell niche (Fig. 2C) (Wang et al 2007).…”
Section: Signal Network and Signaling Centersmentioning
confidence: 99%
“…Splitting of the incisor placode has been observed in vivo in Sostdc1-follistatin double-null mice, in which there is a partial splitting of the placode leading to bifid incisors. In vitro studies using mandible explants have also shown that the main incisor placode is able to split and give rise to two incisors after activin or noggin treatments (Munne et al, 2010).…”
Section: Introductionmentioning
confidence: 99%